Investigation of dielectric properties of urine for pregnancy and bladder cancer detection / Zhu Chaozhe - Zhu , Chao Zhe (2020)
Detection and monitoring of pregnancy and bladder cancer are important for medical treatment and nursing. Urine has diagnostic and prognostic values for pregnancy and bladder cancer due to the presence of biomarkers. This study investigated the dielectric properties of human urine and compared them between two groups: 1) non-pregnant healthy female volunteers and pregnant healthy female volunteers, and; 2) healthy subjects and patients with bladder cancer. An open-ended probe network analyzer was used to measure the urine dielectric constant (Ɛ’) and dielectric loss (Ɛ’’) at microwave frequency ranging from 0.2GHz to 50GHz at 25˚C (room temperature), 30˚C and 37˚C (body temperature). Urine samples from 110 non-pregnant healthy female volunteers and 110 pregnant counterparts were collected to determine the correlation between human chorionic gonadotropin (hCG) hormone levels and dielectric properties. For the bladder cancer study, 35 healthy subjects and 35 patients were recruited from the University of Malaya Medical Center (UMMC). In the analysis of results, subjects and patients with the presence of glucose, protein, bacteria, ketone or hemoglobin in urine were excluded. As a result, 30 healthy subjects and 30 pregnant women were involved for the pregnancy study while 10 healthy subjects and 10 subjects with bladder cancer were involved for the bladder study. Generally, the dielectric properties of urine decreased with temperature before the crossing point, and they increased again after the crossing point. In the study of pregnancy, the Ɛ’ and Ɛ’’were observed to be significantly different between the urine samples of the two groups across all three temperatures. The urine of pregnant women had significantly lower Ɛ’ than non-pregnant women (p<0.05), while Ɛ’’ was significantly higher in pregnant women (p<0.05). They correlated positively with hCG levels at low frequencies (rmax=0.868, f=2.4GHz) but negatively at high frequencies (rmax=-0.877, f=46.2GHz). In cases of bladder cancer, the dielectric properties were generally lower in healthy subjects compared to patients, especially at 25°C. Similar to pregnant women, they decreased with temperature before the crossing point and increased thereafter. Statistically significant differences in Ɛ’ and Ɛ’’ were observed between healthy subjects and patients (P<0.05). A high level of correlation was observed between urinary exfoliated urothelial cells and the dielectric properties of the urine at 25°C. The Ɛ’ correlated negatively with urinary exfoliated urothelial cells (rmax=-0.662, f=5GHz) while Ɛ’’ correlated positively with urinary exfoliated urothelial cells (rmax=0.664, f=40.6GHz).